Adaptive Reuse Aspects of Creativity in South Asian Cultural History - Freschi, Elisa (Harrassowitz Verlag, 2017)
The present volume explores a specific aspect of creativity in South Asian systems of knowledge, literature and rituals. Under the heading of "adaptive reuse," it discusses the relationship between innovation and perpetuation of earlier forms and contents of knowledge and aesthetic expressions within the process of creating new works. Although this relation rarely became the topic of explicit reflections in the South Asian intellectual traditions, it is here investigated by taking a closer look at the treatment of older materials by later authors.